First characterisation of chrysanthemum virus B infecting chrysanthemum in Thailand and development of colourimetric RT-LAMP for rapid and sensitive detection - Supakitthanakorn Salit; Mochizuki Tomofumi; Vichittragoontavorn Kanjana; Kunasakdakul Kaewalin; Thapanapongworakul Pilunthana; Ruangwong On-Uma (Folia Horticulturae, 2022)
Chrysanthemum is among the world's most important ornamental plants because of its high economic and cultural value. Our report is the first to describe the detection of chrysanthemum virus B (CVB) in chrysanthemum leaf samples collected from Thailand, which showed yellowing and mild mottling symptoms. The coat protein sequences of CVB isolated in this study share 95.15% identity with previously characterised CVB isolates. Biological indexing found that CVB induced both local and systemic symptoms in tobacco plants, while petunia displayed systemic symptoms. To improve the rapidity and sensitivity of CVB detection, the loop-mediated isothermal amplification (LAMP) technique was developed. LAMP detection was found to be optimal when incubation was conducted at 65 °C for 45 min, wherein the LAMP reaction demonstrated 106 times higher sensitivity than polymerase chain reaction. To simplify the interpretation of results, we designed the method such that a positive result is clearly indicated based on a change of colour (colourimetry), from pink to yellow, as observed visually and via gel electrophoresis. To our best knowledge, this is the first report on the characterisation of molecular, biological and morphological characteristics of CVB infecting chrysanthemum in Thailand, along with the development of colourimetric RT-LAMP for improving detection efficiency.